2014
DOI: 10.1007/s00784-014-1276-4
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of relaxin receptors in the PDL by biophysical force

Abstract: Rln and Rxfps may serve as a PDL turnover molecule complex to control orthodontic tooth movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…To compare bone destruction, the distance between the first and second molars was measured. The right side was sham operated and used as a control …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare bone destruction, the distance between the first and second molars was measured. The right side was sham operated and used as a control …”
Section: Methodsmentioning
confidence: 99%
“…Cells were plated onto BioFlex culture plates at 3 × 10 5 cells per well and subjected to the strain of maximum 12% elongation at 6 cycles/min. For compression, cells were plated onto 6Φ dishes at a density of 3 × 10 5 cells per dish and subjected to a compression force of 2.5 g/cm 2 by placing cover glasses with titanium discs on them …”
Section: Methodsmentioning
confidence: 99%
“…GPCRs have been reported to be involved in the majority of cellular responses like bone remodeling, nerve transmission, inflammation, and homeostasis 32 . Previous reports revealed that CC chemokine receptor 5, relaxin family peptide receptors 1 and 2, known as the GPCRs, controlled PDL tissue remodeling during orthodontic tooth movement 33,34 . Our previous study also demonstrated that mechanical loading regulated the proliferation and osteo/cementblastic differentiation of human PDL stem cells through a kind of GPCRs, AT2 35 .…”
Section: Discussionmentioning
confidence: 81%
“…32 Previous reports revealed that CC chemokine receptor 5, relaxin family peptide receptors 1 and 2, known as the GPCRs, controlled PDL tissue remodeling during orthodontic tooth movement. 33,34 Our previous study also demonstrated that mechanical loading regulated the proliferation and osteo/cementblastic differentiation of human PDL stem cells through a kind F I G U R E 3 Expression of β2-AR in HPDLCs.…”
Section: Discussionmentioning
confidence: 92%
“…Seven‐week‐old male Sprague Dawley rats, weighing 170–190 g, were randomly and evenly divided into the following groups: days 1, 2 and 6 after BTM. The left upper first molar (M1) was moved mesially by applying a coil spring (Supplement 1A) (Lee et al, 2015; Yang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%